Effects of supplementing saponins from Brachiaria decumbens Stapf on broiler growth and production performances - Alghirani, Mohamed M. (2022)
Although using antibiotics as a growth promoter leads to improve the poultry industry, it is also considered as one of contributing factors that affect human health through antimicrobial resistance. For that reason, using in-feed antibiotics as a promoter has been banned in developed countries including Malaysia due to their harmful effects on humans. Hence, finding alternatives of using antibiotics as growth promotion and improving poultry health care has become necessary. Phytobiotics (herbs and their natural plant extracts) are one of the alternatives that have been used as feed additives in the poultry industry due to their several benefits including improving the digestibility and feed intake leading to enhance the growth performance, as well as playing a substantial role in poultrys’ health in terms of its antimicrobial activity, immune stimulant, antioxidant, gut microflora manipulation, nutrigenomics effect, anti-stress properties, and cholesterol-lowering effect. Therefore, this study aims to determine the effect of three different phytobiotics supplementation in enhancing the production performance of commercial broilers reared under tropical environments. A total of 300 day-old male Ross 308 were randomly assigned to six different dietary treatments with 5 replicates consisting of 10 broilers per replicate. The dietary treatments consist of T1: commercial feed without antibiotic (negative control) and T2: commercial feed added with 100mg/kg oxytetracycline (positive control). T3, T4, T5, and T6 were fed with commercial feed supplemented with 25mg/kg, 50mg/kg, 75mg/kg, and 100mg/kg of powdered Yucca Shidigera (A) respectively in both starter and finisher diets. Throughout the 42-day feeding trial, body weight and feed intake were recorded weekly for each replicate to calculate the body weight gain and FCR. A total of 10 broilers were randomly selected and slaughtered from each treatment during the starter and finisher phases to measure nutrient digestibility, gut histomorphology, cecal microflora population, carcass characteristics, meat quality, as well as blood biomarkers and biochemistry. The same experimental design was conducted for another two more studies using dried Brachiaria decumbens leaves (B) and B. decumbens saponins extract (C). The results showed significant differences (p<0.05) in the growth performance, nutrient digestibility, gut histomorphology, cecal microflora, carcass characteristics, meat quality, blood biomarkers and lipid profile in studies A, B, and C during the starter and finisher phases. T6 broilers supplemented with 100 mg/kg of Y. Schidigera saponins (A), T3 broilers supplemented with 25 mg/kg of B. decumbens (B), and T6 broilers supplemented with 100 mg/kg B. decumbens saponins extract (C) showed a superior growth performance with the highest body weight and body weight gain leading to the best FCR. The apparent ileal digestibility of fiber, protein, and ether extract was the highest, while the digestibility of dry matter and ash were the lowest as compared to the other treatments. Longer villi height and shorter crypt depth with different cecal microbial populations were also observed. Besides, T6, T3, and T6 broilers from experiments A, B, and C respectively exhibited the highest carcass values with superior meat quality. However, those same treatments showed lower acute phase proteins, corticosterone, heat shock protein, and serum lipid profile concentrations in contrast to the other broiler treatments. In conclusion, commercial broilers supplemented with 100 mg/kg of Y. Schidigera saponins, 25 mg/kg of B. decumbens, and 100 mg/kg B. decumbens saponins extract demonstrated better results of growth performance, nutrient digestibility, gut histomorphology, cecal microflora, carcass characteristics, meat quality, and blood parameters under tropical conditions. However, based on the overall findings, 100 mg/kg of B. decumbens saponins extract was the best saponins concentration, which can be used as a potential additive to reduce or replace the use of antibiotics in broiler feeds.